2016
DOI: 10.3390/diseases4040034
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Nrf2/ARE Antioxidant System in Preventing Cardiovascular Diseases

Abstract: It is widely believed that consuming foods and beverages that have high concentrations of antioxidants can prevent cardiovascular diseases and many types of cancer. As a result, many articles have been published that give the total antioxidant capacities of foods in vitro. However, many antioxidants behave quite differently in vivo. Some of them, such as resveratrol (in red wine) and epigallocatechin gallate or EGCG (in green tea) can activate the nuclear erythroid-2 like factor-2 (Nrf2) transcription factor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 109 publications
3
72
0
1
Order By: Relevance
“…19) In response to irreversible mitochondrial dysfunction, the ratio of Bcl-2 to Bax is reversed, subsequently triggering cell death and organ dysfunctions. 21) In our study, we observed a decrease in ROS level and a re-balance in the oxidation/redox system in CTRP12-overexpressing cells. These phenomena ameliorated oxidative stress and may have contributed to the repair of the oxidation/redox system.…”
Section: Discussionsupporting
confidence: 58%
“…19) In response to irreversible mitochondrial dysfunction, the ratio of Bcl-2 to Bax is reversed, subsequently triggering cell death and organ dysfunctions. 21) In our study, we observed a decrease in ROS level and a re-balance in the oxidation/redox system in CTRP12-overexpressing cells. These phenomena ameliorated oxidative stress and may have contributed to the repair of the oxidation/redox system.…”
Section: Discussionsupporting
confidence: 58%
“…Nrf2 is one of the antioxidant genes that received high level of attentions. While Nrf2-mediated cardiac protection has commonly been reported in various studies (Deng et al, 2013;Smith et al, 2016;Erkens et al, 2018), the mixed roles of Nrf2 in various pathogenesis process and inflammation have also been reported (Satta et al, 2017;da Costa et al, 2019;Pompili et al, 2019). Specifically, negative effects of Nrf2 in cardiovascular diseases were reported (Barajas et al, 2011;Harada et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Among many bioactive compounds of walnut, it also contains bioactive polyphenols pedunculagin and ellagitannins, which were reported to indirectly activate the antioxidant response elements (AREs), possibly via the Nrf2 pathway (Hardman, 2014;Le et al, 2014;Smith et al, 2016). This indirect mechanism of ellagitannins is regulated by the gut microbiota, through being hydrolyzed to release the ellagic acid, and then, converted to urolithins A, and B or other derivatives of urolithins that could be circulated through the blood to reach the target tissue and organs (Sánchez-González, Ciudad, Noé, & Izquierdo-Pulido, 2017).…”
Section: F I G U R Ementioning
confidence: 99%